Enhancing Research Competence of Islamic Religious Education Teachers through the Mentoring Model in the Era of Digital Technology - Asbi amrullah (Indonesian Journal of Education and Social Studies, 2023)
This research aims to investigate the effectiveness of implementing the mentoring model in improving the research competence of Islamic Religious Education (PAI) teachers in the era of digital technology. This qualitative research uses a phenomenological approach to dissect the reality of PAI teachers' awareness and experience in conducting research, explore the impact of mentoring activities in improving PAI teachers' research competence and explore the role of digital technology in supporting the improvement of their research competence. Authentic and valid data collection was obtained through interviews, observation and documentation. Informants were selected using a purposive sampling technique, taking into account their motivation and interest in conducting research, employment status (ASN), which requires self-development in conducting research, and skills in using IT technology sophistication. Data analysis techniques are carried out through data analysis and field interpretation, analysis and interpretation after data collection, and the development of coding categories. The research results show that (1) the mentoring model effectively increases understanding and (2) PAI teachers' skills in conducting research. Apart from that, (3) research subjects' motivation, cognition and conation (willingness) are the sine qua non in carrying out mentoring. Also, digital technology is crucial in facilitating interactive relationships between mentor-mentees. The implication of this research is a deeper understanding of the motivations, perceptions, and experiences of PAI teachers in following the mentoring model.